Fusarium oxysporum and F. verticillioides associated with damping-off in Pinus spp. - Maciel, Caciara; Walker, Clair; dos Santos, Ricardo; Muniz, Marlove Fátima; Brum, Daniele (Revista Ciência Agronômica, 2016)
Occurrence of Fusarium spp. is one of the problems, most limiting to growth of seedlings, in nurseries. This pathogen can be transmitted via seeds and causes damages to the seedlings during pre- and post-emergence stages. The present study aimed to identify Fusarium spp. at the species level based on morphological and molecular characteristics and to verify the pathogenicity of these isolates in seeds lots of Pinus elliottii and P. taeda. For this, we used two Fusarium isolates and five lots of Pinus spp. seeds. Morphological characterization was performed based on a key, specific to Fusarium spp. identification, whereas, molecular identification was carried out by amplification and sequencing of the regions from internal transcribed spacer (ITS) and the elongation factor 1-α (tef1). The pathogenicity test was conducted through the contact of the seeds with fungal culture for 48 h, followed by sowing them in sand. The variables evaluated were emergency speed index, percentage of emergency, non-emergency seeds, symptomatic seedlings, and seedling damping-off. One isolate, F1UFSM, was identified as F. verticillioides and another isolate, F2UFSM, was identified as F. oxysporum. Both the isolates were pathogenic to the seeds of Pinus spp., causing a reduction in the percentage of emergence and seedling damping-off.